Effects of video games on aggressive thoughts and behaviors during development - Koojimans, Thomas A.
The explosion of the video game industry in the past decade has had many people questioning the content of the games being released. The main concern is that of violence and violent acts within the games. The newest generation of games is so realistic that the line "simulations" and video games has greatly been blurred. They are so realistic that the United States government has even released a game, entitled America's Army, to help train the next generation of military specialists. In the late 1990's a large number of high-school shootings were blamed on violent games, the most devastating being the shooting at columbine High School in Colorado in 1999. These shootings raise a valid concern that violent video games may be affecting the aggression of children and developing adolescents.
Includes bibliographical references.
Keywords: Aggressiveness; Video games